Primary insomnia: New aspects of diagnosis and differential diagnosis, aetiology and pathophysiology and psychotherapy - Riemann, D; Spiegelhalder, K; Vorderholzer, U; Vorderholzer, U; Kaufmann, R; Kaufmann, R; Seer, N; Seer, N; Klöpfer, C; Klöpfer, C; Hornyak, M; Hornyak, M; et al. (2007)
This review article focusses on the state of the art of research and clinical work with respect to primary insomnia. The ICSD-2 is a new diagnostic classification system encompassing a separate chapter on insomnias. Furthermore, the research diagnostic criteria (RDC) for insomnia, having been recently published, will be of relevance for future research in the field of insomnia. The focus of etiological and pathophysiological theories is the hyperarousal concept. This concept is based on the assumption that patients with chronic primary insomnia display a psychophysiological arousal, manifested for example in increased cortisol secretion or enhanced fast frequencies in the sleep EEG. On a molecular genetic level alterations in the adenosine system could be at the core of the hyperarousal. New psychological concepts of primary insomnia focus on attention processes which might play a role for the chronic course of insomnias. Also in detail discussed will be psychotherapeutic concepts, especially cognitive behavioural strategies for the treatment of primary insomnia. These concepts have been subjected to rigorous evidence based testing and can claim a high degree of scientific evidence. © 2007 Steinkopff-Verlag.